Financial Crime Among Polish Workers in the Years 1945-1956 - Jędrzej Chumiński (Studia Historiae Oeconomicae, 2017)
The subject of this article is financial crime among workers, in particular industrial workers who were supposed to be the “vanguards” of the new political system created in Poland after the year 1944. The paper will concentrate on theft in industrial plants and its motivations. This text also discusses the speed with which these negative – both for the economy and the Polish society – phenomena were shaped in the times when the experience of occupation and the new political experiences created unique circumstances their emergence.